A Comparative Study of Diathermy, Microdebrider, and Coblation-Assisted Inferior Turbinate Reduction in Patients with Inferior Turbinate Hypertrophy - PP, Marva; Senniappan, Shivakumar (Journal of Neonatal Surgery, 2025)
Background:Inferior turbinate hypertrophy (ITH) is a leading cause of nasal obstruction, significantly affecting breathing and quality of life. Several surgical techniques, including diathermy, microdebrider-assisted reduction, and coblation-assisted reduction, are employed for turbinate reduction. However, their comparative efficacy and safety remain under debate. This study aims to evaluate and compare these techniques in terms of symptom relief, complications, and postoperative recovery. Objectives:To compare the effectiveness of diathermy, microdebrider, and coblation-assisted inferior turbinate reduction in improving nasal obstruction, assessing postoperative complications, and determining the most effective and least invasive technique for managing ITH. Methods:A prospective, comparative study was conducted on 90 patients diagnosed with inferior turbinate hypertrophy and scheduled for surgical reduction. Patients were randomly assigned into three groups (n = 30 each) based on the procedure performed: Group D: Diathermy-assisted reduction. Group M: Microdebrider-assisted reduction. Group C: Coblation-assisted reduction. Preoperative and postoperative evaluations included Nasal Obstruction Symptom Evaluation (NOSE) scores, peak nasal inspiratory flow (PNIF) measurements, and nasal endoscopy findings. Follow-ups were conducted at 1 week, 1 month, and 3 months postoperatively to assess symptom improvement, crusting, bleeding, and patient satisfaction. Statistical analysis was performed using ANOVA and chi-square tests, with p < 0.05 considered significant. Results:All three techniques resulted in a significant reduction in NOSE scores and improvement in PNIF measurements (p < 0.05). Coblation-assisted reduction showed the greatest improvement in nasal patency and minimal postoperative discomfort, followed by microdebrider-assisted reduction, while diathermy had the highest rates of crusting and postoperative discomfort. Bleeding and nasal dryness were more frequently reported in the diathermy group compared to the other two groups. Conclusion:Diathermy, microdebrider, and coblation-assisted techniques effectively reduce inferior turbinate hypertrophy and improve nasal obstruction. However, coblation-assisted reduction demonstrated superior outcomes, including minimal complications, faster recovery, and higher patient satisfaction, making it the preferred technique. Microdebrider-assisted reduction also showed favorable results, whereas diathermy, despite its effectiveness, had higher postoperative discomfort and crusting rates. These findings suggest that coblation and microdebrider techniques may be better alternatives for turbinate reduction, warranting further research and long-term follow-up studies.